Higher Order Thinking Skills in English Language Teaching: The Case of Colleges of Education in Ghana - Daniel Arkoh Fenyi; Ivy Jones-Mensah (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The teaching and learning of language has, for many years, been centered on the four language competencies- listening, speaking, reading and writing. However, in modern times, the need to train students with critical, analytical, evaluative, creative, and problem-solving skills in order to meet and deal with the complex nature of modern-day challenges and real-life issues has made the teaching and learning of Higher Order Thinking Skills (HOTS) indispensable. This study, therefore, investigates the attitude of language tutors towards the teaching of HOTS. This study has a descriptive qualitative approach. 39 English language tutors from the Colleges of Education who voluntarily availed themselves as participants were recruited for the study. Using semi-structured interviews and classroom observation as data collection instruments, the data were subjected to a thematic analysis. It is revealed that teachers perceive HOTS to be a good concept and hence use strategies such as asking open-ended questions, engaging learners in group works, classroom discussions, lecturing method, asking learners to produce and/or create their own materials and the giving of constructive feedback to implement it. Regardless of all their efforts, teachers face challenges such as incompetency, learner’s low proficiency, learner’s inability to grasp concepts, insufficient and irrelevant teaching materials, time, and financial constraints. The study, therefore, recommends that HOTS be given some more attention in language teaching in Ghana.